Transfers of disadvantage across three generations using latent class associations within families - Adams, Emma K; Hancock, Kirsten J; Mitrou, Francis; Christensen, Daniel; Taylor, Catherine L; Zubrick, Stephen R (My University, 2022)
There is a large volume of research on the persistence of advantage and disadvantage across generations. Intergenerational studies typically address family resources as independent factors, which ignores how risks cluster together and accumulate over time. Using data from the Longitudinal Study of Australian Children, we conducted two latent class analyses to separately identify latent classes based on grandparent and parent characteristics for study children. We then examined the association between our identified latent classes and grandchild educational outcomes in Years 3 to 9. Five distinct latent classes of grandparent characteristics and four latent classes of parent characteristics were identified. There was association between parent and grandparent latent classes indicating intergenerational multiple disadvantage. Grandchildren in at-risk parent latent classes tended to have significantly lower literacy and numeracy scores from Years 3 to 9. The effects of grandparent latent classes were inconsistent. The developmental circumstances of children can be defined using the characteristics of both parents and grandparents, and the role of grandparents on children's development extends beyond the influence they have on parent outcomes. This study highlights that addressing intergenerational transfers of disadvantage requires multiple, integrated and coordinated policy approaches that go beyond individual indicators of disadvantage.
Australian Journal of Social Issues
Keywords: Disadvantage, adversity and resilience; Intergenerational transfer